Global prevalence and case fatality rate of Enterovirus D68 infections, a systematic review and meta-analysis - Fall, Amary; Kenmoe, Sebastien; Ebogo-Belobo, Jean Thierry; Mbaga, Donatien Serge; Bowo-Ngandji, Arnol; Foe-Essomba, Joseph Rodrigue; Tchatchouang, Serges; Amougou Atsama, Marie; Yéngué, Jacqueline Félicité; Kenfack-Momo, Raoul; Feudjio, Alfloditte Flore; Nka, Alex Durand; et al. (PLoS neglected tropical diseases, 2022)
A substantial amount of epidemiological data has been reported on Enterovirus D68 (EV-D68) infections after the 2014 outbreak. Our goal was to map the case fatality rate (CFR) and prevalence of current and past EV-D68 infections. We conducted a systematic review (PROSPERO, CRD42021229255) with published articles on EV-68 infections in PubMed, Embase, Web of Science and Global Index Medicus up to January 2021. We determined prevalences using a model random effect. Of the 4,329 articles retrieved from the databases, 89 studies that met the inclusion criteria were from 39 different countries with apparently healthy individuals and patients with acute respiratory infections, acute flaccid myelitis and asthma-related diseases. The CFR estimate revealed occasional deaths (7/1353) related to EV-D68 infections in patients with severe acute respiratory infections. Analyses showed that the combined prevalence of current and past EV-D68 infections was 4% (95% CI = 3.1–5.0) and 66.3% (95% CI = 40.0–88.2), respectively. The highest prevalences were in hospital outbreaks, developed countries, children under 5, after 2014, and in patients with acute flaccid myelitis and asthma-related diseases. The present study shows sporadic deaths linked to severe respiratory EV-D68 infections. The study also highlights a low prevalence of current EV-D68 infections as opposed to the existence of EV-D68 antibodies in almost all participants of the included studies. These findings therefore highlight the need to implement and/or strengthen continuous surveillance of EV-D68 infections in hospitals and in the community for the anticipation of the response to future epidemics.